Study Questions for the Certified Pesticide Applicator Examination: Natural Areas Weed Management - Ken A. Langeland (EDIS)
The following questions are intended to help prepare you for taking the Natural Areas Weed Management Certified Pesticide Applicator Examination. It should be used along with IFAS publications SP 295 Natural Area Weed Management - A Training Manual for Restricted Use Pesticide Applicators and SP 257 Identification & Biology of Non-Native Plants in Florida’s Natural Areas, which can be obtained from the IFAS Extension Book store by calling 800-226-1764 (local 359-392-1764) or from http://ifasbooks.ufl.edu. For some questions you will need a copy of a Garlon 4 herbicide label, which can be obtained from http://www.cdms.net/manuf/manuf.asp. Answers to all questions can be found in these publications. You will greatly improve your ability to achieve a passing examination score by locating the answers to the study questions and writing them down. This document is SS-AGR-255, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 2005.